Endovascular Treatment May Be Effective in Preventing Recurrence of Ischemic Stroke in Vertebral Artery Stump Syndrome: A Case Series - Ryo Sakisuka; Takumi Morita; Yuya Tanaka; Shinya Hori; Daisuke Shimo; Naoki Hashimura; Takahiro Kuroyama; Yasushi Ueno (Neurointervention, 2024)
Vertebral artery stump syndrome (VASS) is a rare condition that can cause posterior circulation ischemic stroke due to occlusion of the ipsilateral vertebral artery (VA) orifice, resulting in blood flow stagnation and embolus formation. Although there is no established treatment for this condition, we observed 3 cases of VASS out of 326 acute ischemic stroke cases at a single institution from April 2021 to October 2022. Despite the best possible antithrombotic treatment, all 3 patients had recurrent ischemic strokes. One patient underwent drug-eluting stenting of the VA orifice to relieve occlusive flow. The other 2 patients received coil embolization, which resulted in the disappearance of their culprit collateral flow. None of the patients had recurrent ischemic strokes after endovascular intervention. Based on our observations, stenting and coil embolization are effective methods for preventing future recurrences of VASS.